Transport Application of Hybrid Simulation - Frantisek Brumercik; Roman Danko (Communications - Scientific letters of the University of Zilina, 2014)
Simulation of a road or rail vehicle is a very complex task. There are many possibilities to build the mathematical model according to the goals of the simulation. It can be built either as a general full-editable block model, which will cover all possible structures of the vehicle or as a single-purpose model built for the specific structure and its calculation. Each approach can follow suitable results, but the building and calculating time and work consumption can be incomparable.